GAYA PENERJEMAHAN PUISI "INCIDENT" KARYA COUNTEE CULLEN: SEBUAH KAJIAN STILISTIKA - Prihantono, Kahar Dwi (Jurnal Penerjemahan, 2014)
Stylistics theory is an alternative approach in assessing poetry translation. This study investigates the style of both Countee Cullen's poem -"Incident"- as the source text and Taufik Ismail's translation - "Kejadian"- as the target text. Based on a stylistics theory applied to translation proposed by Khomeijani Farahani (2005), both poems as the source of the data are analyzed based on three criteria: the equivalence accuracy, the formal loyalty, and the naturalness of translation. The results of the study proves that there is an obvious gap between them in terms of semantic, pragmatic, and poetic equivalence. In the criterion offormal loyalty, the deviation lies on rhyming pattern. While in the criterion of naturalness, the translator managed to build an easily accepted discourse structure for target text readers.